Arquitetura organizacional: uma proposta para o Hospital Geral de Ipanema - Macieira, Maria Elisa Bastos (2001)
The complexity of either public or private hospital organizations has been demanding continuous efforts from their heads in the search for improvements in the adopted administration methods. The present work has as purpose to accomplish a review of the current administration model of a public hospital, in this case, the Hospital Geral de Ipanema. It analyzes the characteristics of the organizational structure and their impact in the development of the Hospital activities. As a theoretical reference, the concepts and tools of the theory of organizations will be presented, with focus in organizational structure, which provides support to the present study. Finally, it considers that the process of managerial development of the public hospital organizations, as a result of proven experience, should be analyzed taking into account the need of continuous improvements in its organizational structure and administration methods.